Relevansi Filantropi Islam Dalam Meningkatkan Kesejahteraan Masyarakat (Studi kasus : masyarakat disekitar Masjid Al Munawar Tulungagung) - Anita febriani; Nurhadi Syaifudin Zuhri; Muhammad Agus Salim Lutfi; Agus Eko Sujianto (Universitas Islam Darul Ulum Lamongan, 2022)
The existence of philanthropic activities in the State of Indonesia provides a very positive role for the people of Indonesia with the assistance either in the field or philanthropic institutions or organizations that involve philanthropy. Philanthropy itself is the application of one's generosity to one another, where this activity is not based on demands from the state or government but is a form of love between people. In this article, we want to touch on how the form of channeling Islamic philanthropy in the welfare of the people around the Al Munawar Tulungagung mosque, how Islamic philanthropy can make the surrounding community feel good and have a positive impact on people who earn more. Islamic philanthropy here is focused on improving the welfare of the surrounding community in one of the ways that is carried out, namely channeling Islamic philanthropic funds in zakat, infaq, alms, endowments and also in helping poor surrounding communities. In this paper using qualitative research methods which will make it easier to obtain complete data on how to distribute Islamic philanthropy in the welfare of society, which in this study has literary sources from literature studies. In this Islamic philanthropy review the distribution of funds to the surrounding community in the welfare of the community, both channeling funds directly or through mosque intermediaries.